ANXIETY OF QUEEN GORGO IN SNEYDER'S 300 MOVIE (2007): A PSYCHOANALYTIC APPROACH - Pradhipa, Hangga Nur (2011)
The study is to reveal how anxiety reflected in 300 movie directed by Zack Snyder in 2007. The objectives of the study are to analyze the structural elements of the movie in order to identify the unity of the movie and to analyze the anxiety of the major character using psychoanalytic approach. The object of the study is a movie 300 directed by Zack Snyder. In this research the writer employs the descriptive analysis as a type of the research. The data sources divided in two, namely primary data source and secondary data source. The primary data sources are taken from the text of the movie such us dialogues, character action and whole narration which are relevant to the object of analysis. The secondary data source includes the references from some book and internet. The methods of collecting data are observation and library research. The technique of analyzing data is descriptive. The results of the analysis show that firstly, based on the structural analysis, it is clear that in this movie, the director wants to deliver a moral message that it requires a sense of danger in order to make an individual realize the reasonability. Secondly, the psychoanalytic analysis shows that anxiety develops out of a conflict between id, ego and superego resulting in different types of anxieties.